The Relationship Between the Level of Knowledge and Attitudes with Personal Hygiene Behavior During Menstruation in Adolescent - Samosir, Angelika; Widodo, Tri; Nurfianto, Sigit; Trisia, Adelgrit; Jabal, Arif Rahman (Fakultas Kedokteran Universitas Palangka Raya, 2025)
It is very important for every individual, especially adolescents, to acquire knowledge about reproductive health. The general public still considers issues of reproductive health taboo, particularly concerning personal hygiene during menstruation. This results in a lack of knowledge and attitude regarding proper personal hygiene during menstruation. This study aims to determine the relationship between knowledge and attitude with personal hygiene behavior during menstruation among adolescent girls at SMP Negeri 1 Palangka Raya. This research is a quantitative study with a cross-sectional design. The sample used consisted of 91 students from grades VII, VIII, and IX at SMP Negeri 1 Palangka Raya. The instrument used in this study was a questionnaire. Data analysis was performed using the spearman correlation test. The research results showed that (p=0.000; r=0.624) and attitude (p=0.003; r=0.309) are associated with personal hygiene behavior during menstruation in adolescent girls. The strength of the relationship is considered strong between the level of knowledge and personal hygiene behavior, but the strength of the relationship is weak between attitude and personal hygiene behavior. The conclusion of the study is that there is a significant relationship between the level of knowledge and attitude towards personal hygiene behavior during menstruation in adolescent girls at SMP Negeri 1 Palangka Raya.